2001
DOI: 10.1002/1529-0131(200109)44:9<2146::aid-art368>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Defective Fas ligand-mediated apoptosis predisposes to development of a chronic erosive arthritis subsequent toMycoplasma pulmonis infection

Abstract: Objective To determine whether defective T cell apoptosis is associated with the development of a chronic arthritis subsequent to mycoplasma infection, and to determine whether deletion of T cells can prevent the development of this arthritis. Methods B6 wild‐type (B6‐+/+), B6‐lpr/lpr, and B6‐gld/gld mice were infected with Mycoplasma pulmonis. The severity of lymphocytic infiltration and joint damage was evaluated, and the degree of recovery of viable mycoplasma from the spleen and joints was determined. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
1
5
1
2
Order By: Relevance
“…This results in specific induction and elimination of the T cells in the spleen (Figure 6) of the mouse, which prevents their migration into the joint. This is consistent with our previous results using a macrophage-derived APC-FasL cell gene therapy to prevent the development of arthritis in other murine arthritis models (16,31). The present strategy is superior to our previous version, however, since DCs are more resistant to apoptosis than macrophages (54).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This results in specific induction and elimination of the T cells in the spleen (Figure 6) of the mouse, which prevents their migration into the joint. This is consistent with our previous results using a macrophage-derived APC-FasL cell gene therapy to prevent the development of arthritis in other murine arthritis models (16,31). The present strategy is superior to our previous version, however, since DCs are more resistant to apoptosis than macrophages (54).…”
Section: Discussionsupporting
confidence: 91%
“…We have previously described techniques for modifying APCs so that they express specific Ag's along with FasL and have demonstrated that these modified APCs deleted only those T cells that recognize the specific Ag without causing general immunosuppression (29,30). We previously demonstrated that treatment of mycoplasmas-infected B6-generalized lymphoproliferative disease (gld/gld) mice with adenovirus (Ad) FasLtransfected (AdFasL-transfected) APCs derived from Fas-deficient lpr mice (lpr-APC-AdFasL) resulted in a significantly decreased incidence of chronic arthritis (31). We also have shown previously that normal APCs can be…”
Section: Introductionmentioning
confidence: 99%
“…Joints (knee, elbow, ankle, and wrist) tissue and sections using the method we previously described (29). Joints were scored by a blinded observer for chronic arthritis damage based on the criteria we described previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…Dans ces arthrites chroniques, il existe probablement d'autres facteurs immunitaires mal connus qui prédisposent à la chronicité [42]. Récemment, il a été démontré qu'une anomalie de l'apoptose des lymphocytes T peut favoriser l'apparition d'une arthrite chronique dans un modèle murin d'arthrite à mycoplasme [43]. En effet, les souris B6 infectées par Mycoplasma pulmonis ne développent qu'une arthrite transitoire spontanément résolutive [44].…”
Section: Comment Expliquer Le Rôle Arthritogène Des Mycoplasmes ?unclassified
“…En réalité, l'effet de ce superantigène n'a été démontré que pour Mycoplasma arthritidis chez la souris [40]. En fait, il est possible que l'activation lymphocytaire soit amplifiée par une dérégulation de l'apoptose comme cela a été démontré dans le modèle d'arthrite expéri-mentale (souris B6/lpr-lpr et B6/gld-gld) décrit pré-cédemment [43] ou par d'autres anomalies de l'immunité cellulaire observées dans certains DIP humoraux (DICV, déficits avec hyperIgM par anomalie du CD40 Ligand), mais cela n'a pas été démontré. -Les mycoplasmes ont la capacité de pénétrer et de persister dans les cellules de l'hôte, en particulier dans les cellules mononucléées et les cellules fibroblastiques [52].…”
Section: Comment Expliquer Le Rôle Arthritogène Des Mycoplasmes ?unclassified